A 79 dBΩ 1.2 GHz Low-Noise Single-Ended CMOS Transimpedance Amplifier for High-Performance OTDR Applications - Romanova, Agata; Barzdenas, Vaidotas (Electrical, Control and Communication Engineering, 2019)
The work reports on the design and performance of a low-noise low-cost CMOS transimpedance amplifier (TIA). The proposed circuit shall be employed in optical time-domain reflectometers and is implemented using an affordable 0.18 µm 1.8 V CMOS process. The approach preserves the benefits of a classical feedback structure while addressing the noise problem of conventional feed-forward and resistive feedback architectures via the usage of noise-efficient capacitive feedback. Circuit-level modifications are proposed to mitigate the voltage headroom and DC current issues. The suggested design achieves a total gain of 82 dBΩ (79 dBΩ after the output buffer) within the bandwidth of 1.2 GHz while operating with a total input capacitance of 0.7 pF. The simulated average input-referred noise current density is below 1.8 pA/sqrt(Hz) with the power consumption of the complete amplifier including the output buffer being 21 mW.